Ankylosing spondylitis monocytes show upregulation of proteins involved in inflammation and the ubiquitin proteasome pathway. Issue 10 (24th October 2008) - Wright, C; Edelmann, M; diGleria, K; Kollnberger, S; Kramer, H; McGowan, S; McHugh, K; Taylor, S; Kessler, B; Bowness, P
Abstract : Objectives: To determine if peripheral blood monocytes from patients with ankylosing spondylitis (AS) differed in protein expression compared to rheumatoid arthritis (RA) and healthy controls (HC). Methods: Monocyte protein expression was characterised by 2D gel electrophoresis and by label-free quantitative expression profiling, using nano-ultra performance liquid chromatography coupled to electrospray ionisation mass spectrometry (ESI-MS E, where E refers to low/high collision energy switching). Data sets were analysed using the Waters expression profiling system and Ingenuity pathway analysis (IPA). Results: Two-dimensional gel electrophoresis showed upregulation of proteasomal constituents in AS monocytes, including the β subunit of proteasome activator (PA)28. Monocyte expression profiling and IPA showed that significant changes in protein expression within the ubiquitin proteasome pathway (UPP) were restricted to AS monocytes. Statistically significant differences in protein expression involving the leucocyte extravasation, vascular endothelial growth factor, integrin and Toll-like receptor signalling pathways were seen in AS and RA monocytes compared to healthy controls. No evidence of upregulation of proteins involved in the endoplasmic reticulum stress response pathway was found in either AS or RA monocytes. Finally, the PA28 complex was shown to increase the generation of human leucocyte antigen (HLA)-B27 antigenic epitopes by the proteasome in vitro. Conclusions: Our proteomic analyses support the hypothesis that monocytes play an important role in the pathogenesis of AS and RA, and further suggest a specific role in AS for the UPP. Quantitative proteomic expression profiling constitutes a powerful new tool for rheumatology research.